A novel miRNA negatively regulates resistance to Glomerella leaf spot by suppressing expression of an NBS gene in apple. Issue 1 (1st August 2019) - Zhang, Yi; Zhang, Qiulei; Hao, Li; Wang, Shengnan; Wang, Shengyuan; Zhang, Wenna; Xu, Chaoran; Yu, Yunfei; Li, Tianzhong
Abstract: Glomerella leaf spot (GLS) of apple ( Malus × domestica Borkh.), caused by Glomerella cingulata, is an emerging fungal epidemic threatening the apple industry. Little is known about the molecular mechanism underlying resistance to this devastating fungus. In this study, high-throughput sequencing technology was used to identify microRNAs (miRNAs) involved in GLS resistance in apple. We focused on miRNAs that target genes related to disease and found that expression of a novel miRNA, Md-miRln20, was higher in susceptible apple varieties than in resistant ones. Furthermore, its target gene Md-TN1-GLS exhibited the opposite expression pattern, which suggested that the expression levels of Md-miRln20 and its target gene are closely related to apple resistance to GLS. Furthermore, downregulation of Md-miRln20 in susceptible apple leaves resulted in upregulation of Md-TN1-GLS and reduced the disease incidence. Conversely, overexpression of Md-miRln20 in resistant apple leaves suppressed Md-TN1-GLS expression, with increased disease incidence. We demonstrated that Md-miRln20 negatively regulates resistance to GLS by suppressing Md-TN1-GLS expression and showed, for the first time, a crucial role for miRNA in response to GLS in apple.